GitHub Models: Prototyping with AI Models. - Rand-Hendriksen, Morten (linkedin.com, 2024)
Access and develop AI applications with GitHub Models. Experiment with large and small language models from OpenAI, Meta, Mistral, Microsoft, and more in GitHub’s model playground.